Análisis de los materiales ecológicos para las secretarias de la Universidad Técnica de Cotopaxi la Matriz, en el periódo abril-agosto 2015 - Alpusig Endara, Elizabeth Jacqueline (2016)
This research work is about "Analysis of ecological materials for the secretariats, which was carried out through an investigation and with the participation of the secretariats of the Technical University of Cotopaxi, through the methodology used could be determined that the secretariats of the institution do not have knowledge about the benefits advantages and disadvantages which have organic materials within the workplace and that things have to recycle in the office. Once carried out the analysis and interpretation of the results obtained during the implementation of surveys and interviews carried out to the secretariats of the Technical University of Cotopaxi, it has been verified that it is necessary and indispensable to have a broad knowledge on organic materials, which will allow them to enjoy good health of the Secretaries in the labor area. To achieve quality work is the duty of the authorities which provided them a seminar on the use of organic objects, in such a way that secretariats to handle these objects with ease and use it permanently, therefore feel satisfaction as workers which is a benefit for the health of the personnel of the keys